Degradation of 4-Chlorophenol via the meta Cleavage Pathway by Comamonas testosteroni JH5 - Hollender, J. (1997)
Comamonas testosteroni JH5 used 4-chlorophenol (4-CP) as its sole source of energy and carbon up to a concentration of 1.8 mM, accompanied by the stoichiometric release of chloride. The degradation of 4-CP mixed with the isomeric 2-CP by resting cells led to the accumulation of 3-chlorocatechol (3-CC), which inactivated the catechol 2,3-dioxygenase. As a result, further 4-CP breakdown was inhibited and 4-CC accumulated as a metabolite. In the crude extract of 4-CP-grown cells, catechol 1,2-dioxygenase and muconate cycloisomerase activities were not detected, whereas the activities of catechol 2,3-dioxygenase, 2-hydroxymuconic semialdehyde dehydrogenase, 2-hydroxymuconic semialdehyde hydrolase, and 2-oxopent-4-enoate hydratase were detected. These enzymes of the meta cleavage pathway showed activity with 4-CC and with 5-chloro-2-hydroxymuconic semialdehyde. The activities of the dioxygenase and semialdehyde dehydrogenase were constitutive. Two key metabolites of the meta cleavage pathway, the meta cleavage product (5-chloro-2-hydroxymuconic semialdehyde) and 5-chloro-2-hydroxymuconic acid, were detected. Thus, our previous postulation that C. testosteroni JH5 uses the meta cleavage pathway for the complete mineralization of 4-CP was confirmed.